2011
DOI: 10.1007/s12525-011-0072-0
|View full text |Cite
|
Sign up to set email alerts
|

Product type and consumers’ perception of online consumer reviews

Abstract: Consumers hesitate to buy experience products online because it is hard to get enough information about experience products via the Internet. Online consumer reviews may change that, as they offer consumers indirect experiences about dominant attributes of experience products, transforming them into search products. When consumers are exposed to an online consumer review, it should be noted that there are different kinds of review sources. This study investigates the effects of review source and product type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 72 publications
0
72
0
7
Order By: Relevance
“…Due to the organization's low budget, LA Gang Tour's promotion is dependent on online channels, where information is either formed by the organization itself or emerges from public relations, meaning online press releases, international news outlets or consumerbased online word-of-mouth communication (see Table 1). The importance of online newspapers and consumer opinions (here on Facebook), in terms of data credibility and influence when seeking information, was verified by Johnson and Kaye (2004) and Bae and Lee (2011).…”
Section: Study Methodsmentioning
confidence: 89%
“…Due to the organization's low budget, LA Gang Tour's promotion is dependent on online channels, where information is either formed by the organization itself or emerges from public relations, meaning online press releases, international news outlets or consumerbased online word-of-mouth communication (see Table 1). The importance of online newspapers and consumer opinions (here on Facebook), in terms of data credibility and influence when seeking information, was verified by Johnson and Kaye (2004) and Bae and Lee (2011).…”
Section: Study Methodsmentioning
confidence: 89%
“…From this point of view books have transformed from experience goods into search goods or even into a hybrid between experience and search goods (Nakayama, Sutcliffe and Wan 2010). Some researchers (Bae andLee 2011, Huang, Lurie andMitra 2009) have also found that reviews and their effect on perceived helpfulness differ across product types. In terms of buying decisions, customer reviews are a more important source for experience goods than for search goods.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…A review of an experience product is most credible when it appears in an online community and is given more credit than a search product comment when it appears in a consumer-developed review site (Bae, Lee 2011b). …”
Section: Ewom and Credibilitymentioning
confidence: 99%